Cloning and expression of the vegetative insecticidal protein gene of Bacillus thuringiensis in Escherichia coli and its use in bioassay - Bharti, Gunjan; Krishnaraj, P U (Indian Journal of Plant Protection, 2020)
Amplicon restriction fragment length polymorphism (ARFLP) method was used for the identification of a variantÂ of vip3 gene. The variant vip3 related gene was identified in Bacillus thuringiensis. This variant gene is 2370 bp long and codes for a 91-kDa protein (801 amino acids). The amino acid sequence exhibited 99 per cent sequence similarity with vip3Aa. The vip3Aa protein was produced in Escherichia coli and tested against the third instar larvae of Plutella xylostella, where it caused 96.67 per cent mortality.